2006
DOI: 10.1002/ptr.2031
|View full text |Cite
|
Sign up to set email alerts
|

Additional antiprotozoal flavonol glycosides of the aerial parts of Helianthemum glomeratum

Abstract: Bioassay-guided fractionation of the methanol extract of aerial parts from Helianthemum glomeratum afforded five antiprotozoal flavonol glycosides: tiliroside, kaempferol-3-O-(3″,6″di-O-E-p-coumaroyl)-β β β β β -D-glucopyranoside, astragalin, quercitrin and isoquercitrin. The in vitro antiprotozoal assay showed that tiliroside was the most potent antiamoebic and antigiardial compound with IC 50 values of 17.5 µ µ µ µ µg/mL for Entamoeba histolytica and 17.4 µg/mL for G. lamblia. Isoquercitrin showed selectivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 18 publications
(14 reference statements)
3
26
0
1
Order By: Relevance
“…The drug of choice in the treatment of giardiasis is metronidazole (Flagyl), which is among the nitroimidazole derivatives and effective on anaerobic bacteria and protozoa. Other drugs used to treat giardiasis are furazolidone and quinacrine (Harris et al 2001a;Calzada and Alanis 2007). Metronidazole has been used for several decades in the treatment of protozoan, bacterial and fungal infections; nonetheless, there have been some reports regarding the carcinogenic and teratogenic effects on laboratory rats and drug resistance to some isolates of Giardia.…”
Section: Introductionmentioning
confidence: 99%
“…The drug of choice in the treatment of giardiasis is metronidazole (Flagyl), which is among the nitroimidazole derivatives and effective on anaerobic bacteria and protozoa. Other drugs used to treat giardiasis are furazolidone and quinacrine (Harris et al 2001a;Calzada and Alanis 2007). Metronidazole has been used for several decades in the treatment of protozoan, bacterial and fungal infections; nonetheless, there have been some reports regarding the carcinogenic and teratogenic effects on laboratory rats and drug resistance to some isolates of Giardia.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that astragalin and kaempferol-3-O-glucuronide isolated from Vahlia capensis and kaempferol-3-O-glucuronide from Rubus ulmifolius showed antibacterial activity [17]. Antioxidant [6][7][8], antiprotozoal [9], hepatoprotective [18] and glycation inhibitory effects [19] were also observed with these two bioactive compounds. Despite reports on the use of folk medicine together with reports on medicinal potentials of this plant, information on the hepatoprotective activity is unavailable to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 93%
“…India, the abode of Ayurvedic system of medicine, assigns much importance to the pharmacological aspects of many plants. Hepatoprotective effect of some plants like Spirulina maxima [5], Eclipta alba [6], Boehmeria nivea [7], Cichorium intybus [8], Picrorhiza kurroa [9], Maydis stigma (10), Gmelina arborea Roxb. (11) and Manilkara zapota [12] etc.…”
Section: Introductionmentioning
confidence: 99%
“…The more glycosyl of gracillin indicates a stronger ability of the chemical to be dissolved in body fluid resulting in much more easily interact with its target in the parasites. Therefore, it is postulated that the more sugar moiety might be responsible for the higher anthelmintic efficacy of gracillin (Calzada and Alanis 2007).…”
Section: Samplementioning
confidence: 99%